On-Demand Hypermedia/Multimedia Service over Broadband Networks - Christos Bouras; Vaggelis Kapoulas; Paul Spirakis; D Moiras; V Ouzounis; A Tatakis (5th IEEE International Symposium On High Performance Distributed Computing-HPDC-5, Syracuse, New York, USA, 1996)
In this paper we present a uni ed approach for de- livering hypermedia/multimedia objects over broadband networks. Documents are stored in various multimedia servers, while the inline data may reside in their own media servers, attached to the multimedia servers. The described service consists of several multimedia servers and a set of functions that intend to present to the end user interactive information in real-time. Users interact with the service requesting multimedia docu- ments on demand. Various media streams are trans- mitted over dierent parallel connections according to their transmission requirements. The hypermedia doc- uments are structured using a hypermedia markup lan- guage that keeps information of the spatiotemporal re- lationships among document's media components. In order to deal with the variant network behavior, buering manipulation mechanisms and grading of the transmitted media quality techniques are proposed to smooth presentation and synchronization anomalies.